Relational Process Clauses in the Students’ Descriptive Essays - Bahtera Sembiring (Jurnal Bahasa Inggris Terapan, 2020)
This study revealed the result of the analysis of the relational process clauses found on the students’ descriptive essays at the CCU course. The study is aimed at scrutinizing the clauses of the relational process with their roles and lexical verbs realizing the relational process. The data analyzed for the accountable study were 21 descriptive essays. The method applied for the study was the descriptive qualitative one and Systemic Functional Linguistics (SFL) was used as the framework in analyzing the data. The study exposed 5 different roles of clauses as a result. The roles are properties or characteristics with the first place following definition, classification, composition, and function ones in a consecutive way. The study result also acknowledged that relational process clauses are mostly used for describing Properties. This role was realized by two types of relational process clauses –intensive and possessive relational process clauses operating on attributive relational process. However, the relational process occurring in possessive relational process clause was only realized by a single verb have. This indicates that the students have a limited linguistic knowledge which implicates on improving students’ writing descriptive skills. Keywords: relational process clause, descriptive writing, essays, Systemic Functional Linguistics, CCU